KONTRIBUSI BUDAYA ORGANISASI DENGAN KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH PROVINSI SUMATERA BARAT - Refki Yuliarman (Jurnal Bahana Manajemen Pendidikan, 2014)
This research aim to to get information about performance of, Organizational culture by head and also placement by head contribution to Employee performance in Badan Kepegaewaian Daerah Provinsi Sumatera Barat. Population of this research are all of Badan Kepegawaian Daerah Provinsi sumatera Barat amounting 76 people. Level of sampel 55 taken officer  people by using stratified propotional random sampling technique. Instrument of this research questionare which in form of Likert scale. Data analysed by using correlation technique and regresi preceded normalitas test, homogenitas test, linearitas test and also continued with searching the level of organizational culture by head variable contribution to employee performance with result 21,64%, while rest 78,36% influenced by other factor. So, can be concluded that organizational culture by head represent one of factor influencing employee performance in Badan Kepegawaian Daerah Provinsi sumatera Barat. Kata Kunci : Budaya Organisasi ; Kinerja Pegawai